SCIENCE AND POLITICS IN THE COPRODUCTION OF KNOWLEDGE IN THE POLICY CYCLE: EPISTEMOLOGICAL CHALLENGES AND EVIDENCE-INFORMED DIALOGUE IN THE MULTILATERAL GOVERNANCE OF THE COP 30 AGENDA - Hello, Fernando Antonio (RP3 - Revista de Pesquisa em Políticas Públicas, 2025)
Abstract This article examines the growing gap between science and politics, their respective ethos and modus operandi, in public policymaking, within the policy cycle, and among decision-makers, especially in Brazil, where these dimensions interact problematically. Drawing on the specificities of the political and scientific fields, it is found that, although science is vital and objective in its pursuit of facts, decision-making in the political field is also influenced by diverse factors, revealing challenges in the application of scientific knowledge due to the epistemological differences between these two spheres of action and their institutions. Based on a structuralist approach and successive approaches to the issue, the need for innovative approaches that view science, policies, and society as "co-produced" is proposed. In this network of interfaces between actors, starting from a critique of the "Evidence-Based Policy" (EBP) approach, which has been superseded by "Evidence-Informed Policy" (EIP), the importance of dialogue between scientists, society, and decision-makers in the policy cycle is highlighted. In the particular case of COP 30 (Conference of the Parties to the United Nations Framework Convention on Climate Change), held in Belém, Pará, Brazil, in November 2025, incremental advances in better governance are proposed in these forums for complex global issues involving ethical values, legislation, negotiation, government strategies, multilateral agreements, and other policy commitments informed by scientific evidences.